MANFAAT HASIL BELAJAR KETERAMPILAN MENJAHIT TAILOR SEBAGAI KESIAPAN MAGANG DI TAILOR - Tami Latifa; Mally Maeliah (Universitas Pendidikan Indonesia, 2016)
This study examines the benefits of tailor sewing skills learned by the students of Social Parmadi Putra Rehabilitation Center (BRSPP) as the preparation for apprenticeship. Apprenticeship is one of the conditions to completed sewing training program at BRSPP. The purpose of this study is to obtain data in learning Tailor Sewing Skills’s benefit outcomes as an intern in the tailor business. The method which used in this research is descriptive analytic data collection in the form of a questionnaire. The population of this research are students at BRSPP class 2014 with a total respondents amounted to 25 people. The results of this study showed that more than half of the learners are able to understand and master the skills of sewing tailor the material in terms of maintaining and preparing the sewing machine, sewing techniques trousers, and safety. The conclusion of this study shows that tailor sewing skills to provide benefits for the students to prepare tailor apprenticeship.